"Half Here, Half There": Dialogical Selves Among Older Puerto Ricans of the Diaspora. Issue 1 (2nd January 2016) - Guzzardo, Mariana T.; Todorova, Irina L. G.; Adams, Wallis E.; Falcón, Luis M.
Abstract : Puerto Rican adults who moved from Puerto Rico to the U.S. mainland during their youth and have been living in the mainland for several decades provide a multifaceted case for analyzing cultural identity. Our article focuses on a group of Puerto Ricans living in Boston and their discussions of their own cultural identity, including their sense of belonging and home. The current study is based on semistructured interviews with a subsample of 26 participants from a large longitudinal cohort study of 1, 500 respondents. We analyzed data collected through in-depth interviews and use dialogical self theory (DST) as a framework for understanding the multiple discourses in their responses. Three main I-positions that we identify include I-as-Puerto Rican, I-as-realist, and I-as-other. The dialogical process of these I-positions demonstrates the complex connections participants had to place. Findings can inform future studies of acculturation and assimilation among older Puerto Ricans of the diaspora.